1994
DOI: 10.1093/carcin/15.4.787
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of rat liver epithelial tumor cells by monoterpenes does not involve Ras plasma membrane association

Abstract: The role of altered ras oncoprotein (Ras) farnesylation and membrane association in the growth inhibitory effects of several monoterpenes (limonene, perillic acid, perillyl alcohol, menthol, pinene and cineole) was investigated in rat liver epithelial cells. All of the above compounds except cineole inhibited the growth of viral Ha-ras-transformed rat liver epithelial cells (WB-ras cells) at concentrations of 0.25-2.5 mM. These cells, however, were not necessarily more sensitive to these compounds compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Many monoterpenes, including ␣-pinene, may exhibit anticancer activities. 46,48 Based on the current results, we speculate that the major component of gum mastic, ␣-pinene, may be the active compound for repressing AR expression in LNCaP cells, although we cannot rule out the possible involvement of other components in gum. Because other gum resins can be administered systemically for disease treatments in animal models, 46,47 we expect that gum mastic or its active components may be useful in vivo for prostate cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Many monoterpenes, including ␣-pinene, may exhibit anticancer activities. 46,48 Based on the current results, we speculate that the major component of gum mastic, ␣-pinene, may be the active compound for repressing AR expression in LNCaP cells, although we cannot rule out the possible involvement of other components in gum. Because other gum resins can be administered systemically for disease treatments in animal models, 46,47 we expect that gum mastic or its active components may be useful in vivo for prostate cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Limonene studies have also shown antitumor effect against some cancers. The growth of viral Ha-ras-transformed rat liver epithelial cells was inhibited by limonene (Ruch and Sigler, 1994). Limonene also inhibits the development of gastric cancers through increased apoptosis and decreased DNA synthesis (Uedo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…46 and 47). As well, it has been described as a farnesyl-transferase inhibitor that results in the blockage of ras oncoprotein activity (48,49), although this has been challenged (50,51). Importantly, in all these cases relatively high concentrations of POH (well above 100 mmol/L) are required to achieve 50% inhibition of target activity (see also Fig.…”
Section: Discussionmentioning
confidence: 99%